The impact of international terrorism on the right to life in Iraq after 2003 - Mahmood, Mohammed Salman (2014)
Terrorism is a cancer and it is not in the interest of the nations, because it takes away their right to live freely.Following the event of September 11, there have been violations of international conventions and usages, human rights and freedoms, which prompted countries globally to come up with laws to protect civil freedoms.In the context of Iraq, the Government came up with the Iraqi Anti-Terrorism Act No.13 of 2005 and the Iraqi Constitution of 2005 to address the issue of terrorism.The aim of this paper is to address the impact of international terrorism on the right to life in Iraq after 2003.The methodology adopted in this paper is a doctrinal legal research, namely library-based research, depending on books, articles, legal diaries and Internet resources. This paper concludes that international terrorism has indeed affected Iraqis right to life after 2003. Hence, there is a need to protect this fundamental right by relooking into the Iraqi Constitution of 2005 and the Iraqi Anti-Terrorism Act No.13 of 2005. For instance under the Iraqi Anti-Terrorism Act No.13 of 2005 there is no clear definition of the terms "terrorism" and "terrorist acts."